Structural characterization and immunomodulatory activity of a new polysaccharide from jellyfish. (1st March 2017) - Li, Qiang-Ming; Wang, Jing-Fei; Zha, Xue-Qiang; Pan, Li-Hua; Zhang, Hai-Lin; Luo, Jian-Ping
Highlights: A homogenous polysaccharide (JSP-11) was isolated from jellyfish. The structural features of JSP-11 were characterized. The activation of macrophages by JSP-11 and the related mechanism were studied. Abstract: A new polysaccharide (JSP-11) with a molecular weight of 1.25 × 10 6 Da was extracted and purified from jellyfish. Monosaccharide analysis showed that JSP-11 was composed of mannose, galactose and glucuronic acid with a molar ratio of 2.18:1.00:1.94. According to the analysis of fourier transform-infrared spectroscopy, methylation analysis, and NMR spectroscopy, JSP-11 was determined to contain a linear backbone which consisted of (1 → 3, 6)-linked β -d -Man p and (1 → 6)-linked β -d -Gal p . The branch of (1→)-linked α-d -Glc p A was attached to the C-3 position of (1 → 3, 6)-linked β -d -Man p in the backbone. The immunomodulatory assay exhibited that JSP-11 could significantly enhance the viability of RAW 264.7 macrophage cells, and promote the release of NO, TNF-α, and IL-1 β via activating NF- κ B, MAPKs and PI3K/Akt signal pathways.